2010
DOI: 10.1007/s00253-010-2746-5
|View full text |Cite
|
Sign up to set email alerts
|

Electricity generation from mixed volatile fatty acids using microbial fuel cells

Abstract: Fermentative hydrogen production, as a process for clean energy recovery from organic wastewater, is limited by its low hydrogen yield due to incomplete conversion of substrates, with most of the fermentation products being volatile fatty acids (VFAs). Thus, further recovery of the energy from VFAs is expected. In this work, microbial fuel cell (MFC) was applied to recover energy in the form of electricity from mixed VFAs of acetate, propionate, and butyrate. Response surface methodology was adopted to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(28 citation statements)
references
References 36 publications
3
25
0
Order By: Relevance
“…in MFCs fed with short-chain fatty acids is sometimes reported (Teng et al, 2010;Xing et al, 2010), their ecophysiological roles in the MFCs are largely unknown. In general, members of the genus Hydrogenophaga are known to be aerobic bacteria that can oxidize hydrogen but not acetate (Kämpfer et al, 2005).…”
Section: Syntrophic Acetate-oxidizing Microbes In Mfcsmentioning
confidence: 99%
“…in MFCs fed with short-chain fatty acids is sometimes reported (Teng et al, 2010;Xing et al, 2010), their ecophysiological roles in the MFCs are largely unknown. In general, members of the genus Hydrogenophaga are known to be aerobic bacteria that can oxidize hydrogen but not acetate (Kämpfer et al, 2005).…”
Section: Syntrophic Acetate-oxidizing Microbes In Mfcsmentioning
confidence: 99%
“…Except for Spirochaetes the bacterial phyla found here (Bacteroidetes, Firmicutes and Proteobacteria) have been repeatedly identified on bioanodes [42,[51][52][53][54]. After the first 23 days of operation, the three biofilms sampled were dominated by three different orders: Desulfuromonadales for reactor 1, unidentified Bacteroidetes for reactor 2 and Bacteroidales for reactor 3.…”
Section: Microbial Community Analysismentioning
confidence: 64%
“…It was demonstrated that MFCs could generate electricity from leachate, but the excessive organic residues may decrease Coulombic efficiency (CE), especially in membraneless MFC systems . It was reported that increasing proportions of butyrate and propionate could decrease power density and CE from 1.9 to 1.0 W m -3 and from 34 to 20 %, respectively (Teng et al 2010). Although BES could effective remove organic contaminants in leachate with electricity generation, the study of nutrient removal is very limited.…”
Section: Introductionmentioning
confidence: 99%